2D:4D does not predict economic preferences: Evidence from a large, representative sample - Levent Neyse; Magnus Johannesson; Anna Dreber (Deutsches Institut für Wirtschaftsforschung (DIW), 2020)
The digit ratio (2D:4D) is considered a proxy for testosterone exposure in utero, and there has been a recent surge of studies testing whether 2D:4D is associated with economic preferences. Although the results are not conclusive, previous studies have reported statistically significant correlations between 2D:4D and risk taking, altruism, positive reciprocity, negative reciprocity and trust. Many "researcher degrees of freedom" and small sample sizes are important limitations of previous studies. We present results from a pre-registered large sample study testing if 2D:4D is associated with economic preferences. Data were collected in a representative sample of adults in the German Socioeconomic Panel-Innovation Sample (SOEP-IS), in a sample of about 3,450 respondents (about 5 times larger than the previously largest study in this field). We find no statistically significant association between 2D:4D and economic preferences in the largest study to this date on the topic.
Keywords: D03; D87; 330; Economic behavior; prenatal hormones; testosterone; digit ratio